Systematics of Ecuadorian anoles: Anolis bitectus Cope, 1864 and A. lemniscatus Boulenger, 1898, two junior synonyms of A. binotatus Peters, 1863 (Reptilia: Squamata: Anolidae) - Ayala-Varela, Fernando; Poe, Steven; Posse-Sarmiento, Valentina; Fläschendräger, Axel; Köhler, Gunther; Torres-Carvajal, Omar (Zootaxa, 2025)
More than a century ago, three species of lizard with similar morphology were described from Ecuador: Anolis binotatus Peters 1863, A. bitectus Cope 1864, and A. lemniscatus Boulenger 1898. We studied the genetics, type material and morphological variation throughout the range of these forms to evaluate the taxonomic status of these names. Our phylogenetic analyses, based on mitochondrial genes such as COI and ND2, and a nuclear gene such as RAG1 revealed three geographically structured clades (northern, central and southern) similar in morphology and coloration, that did not correspond to the three species in question. Similarly, we found no justification for recognizing all three species based on examination of type material and comparisons of morphology across the geographic range of specimens assigned to the three species. Although there were significant differences in snout length and the number of scales between the interparietal and supraorbital semicircles among recovered molecular clades, we do not consider these differences as diagnostic at the species level. Therefore, we propose that A. binotatus is a senior synonym of both A. bitectus and A. lemniscatus. We provide a new description and variation of A. binotatus, including hemipenis, natural history, geographic distribution and conservation status.